Shedding the blanket of immunity: a commentary on the global principle of ending impunity, realpolitik, and legal precedent - Rothe, Dawn (Crime, law and social change, 2010)
Over the course of the past two decades, there have been attempts by governments and the international political community to limit the scope of immunity granted to heads of states. Nevertheless in recent years we have witnessed former heads of state being brought to justice through ad hoc international criminal tribunals and the permanent International Criminal Court. Yet, head of state immunity remains one of the leading points of contention in international law. The issue is further compounded with the multiplicity of national systems that fall short of their duty to prosecute foreign heads of state if they have committed heinous crimes, those considered jus cogens which constitute peremptory norms. As such, there is a need to examine immunity from prosecution by another state separately from immunity from an international tribunal and/or court. This is especially the case given the problems of initiating ad hoc tribunals and the limited abilities of the ICC, highlighting the need to ensure cooperation of states’ willingness and ability to prosecute. In doing so, I draw from the infamous case of former President of Chile, Augusto Pinochet, and subsequent attempts by national systems to hold accountable foreign heads of state. I conclude by suggesting that the optimism for ending impunity is not only premature, but misguided given the realpolitik surrounding national progression for ending head of state immunity and ensuring their legal obligations to prosecute.